PHILOSOPHY AND HUMANISM DURING THE REIGN OF MIRZO ULUGBEK - Mavlyanov Ulugbek Saidkasimovich (International Journal of Innovations in Engineering Research and Technology, 2021)
Mirzo Ulugbek is one of the unique persons in the Timurid dynasty, who made an invaluable contribution to the development of science and culture. Mirzo Ulugbek is the son of Shahrukh and the grandson of the great Tamerlane. The main goal of the scientificarticle is to study the scientific and cultural heritage in the Timurids era and to create the invaluable work “Star tables of Ulugbek” that causes admiration and surprise of the whole world.